Effects of clearcutting on species composition and community renewal of Rhododendron shrubs in northwest Guizhou Province, China - Zhang, Yaoyao; Zhao, Xuechun; Wang, Lingjun; Wang, Zhaoyi; Shuai, Honggang; Wang, Yuefeng; Jin, Baocheng; Chen, Chao (Frontiers in Ecology and Evolution, 2023)
Tree base sprouting is the main reproduction and expansion mode of Rhododendron plants. By leveraging the plot survey method, the species composition, community renewal, and species diversity in three Rhododendron shrub communities in control, and before and after clearcutting (CK, D3yr, and D6yr, respectively) were studied.Moreover, the dissimilarity of Rhododendron communities in CK, D3yr and D6yr were analyzed. The results showed that there were 26 plant species belonging to 14 families and 22 genera, in 3 communities in total, with 19 species of shrub plants and 7 species of herbaceous plants. The number of species increased from 13 in CK to 23 in D3yr and then decreased to 20 in D6yr. The height and coverage of D3yr and D6yr reached 39.3% and 58.9% of that of CK, respectively. The relative height of CK, D3yr, and D6yr was 43.79%, 65.4%, and 58.54%, respectively. The coverage of D3yr and D6yr reached 60.8% and 114.70% of that of CK, respectively. The relative coverage of CK, D3yr, and D6yr was 19.05%, 83.24%, and 77.32%, respectively. The important value of Rhododendron plants in the communities increased from 0.42 in CK to 0.74 in D3yr, and then decreased to 0.67 in D6yr. The α diversity in the shrub layer of D3yr and D6yr were generally lower than those of CK except Pielou evenness index. The β diversity indicates that the similarity between CK and D3yr was lower, that between CK and D6yr was moderate, and that between D3yr and D6yr was higher. The sprouting height and coverage of Rhododendron plants was significantly correlated with age and sprouting time. The sprouting ability of Rhododendron plants increased first and then decreased with age, while the sprouting ability of Rhododendron plants with age of 10-12 years was the strongest. Clearcutting measures cand improve the dominance of Rhododendron plants in the communities, promote the sprouting and renewal of Rhododendron population, and accelerate the succession rate of communities.